Development of a remote radio unit and optical access link for the ORCIP C-RAN testbed - Brandão, Bruno Tavares (2020)
The new generations of mobile communications bring new challenges for their transport. The support for multiple services, the high bandwidth and the low latency are the most important requirements. This dissertation explores the use of analog radio-over-fibre transmission in the ORCIP testbed. Low cost SFP optical transceivers modified for analogue signal transmission, are studied and characterised. Additionally, a remote radio unit that contains an RF frontend and the optical transceivers is designed. The RF frontend is designed for operation over band 7 of 4G-LTE. The performance of both RF frontend and optical link is assessed using a real 4G-LTE signal.